h - Roychoudhury, Abhik; D$1 (BSouza, Meenakshi.s; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 9th International Colloquium on Theoretical Aspects of Computing, ICTAC 2012 held in Bangalore, India, in September 2012. The 16 revised full papers presented together with the abstracts of three keynote talks were carefully reviewed and selected from 73 submissions. The papers cover various topics related to both theoretical aspects of computing and the exploitation of theory through methods and tools for system development.
Symbolically Bounding the Drift in Time-Constrained MSC Graphs -- A Compositional Hierarchical Monitoring Automaton Construction for LTL -- How to Translate Efficiently Extensions of Temporal Logics into Alternating Automata -- Correctness of Object Oriented Models by Extended Type Inference -- Non-termination Sets of Simple Linear Loops -- Definite Expression Aliasing Analysis for Java Bytecode -- Using Semantics Specified in Maude to Generate Test Cases -- A Locally Nameless Representation for a Natural Semantics for Lazy Evaluation -- Modal Process Rewrite Systems -- S-Narrowing for Constructor Systems -- Data Privacy Using MASKETEERTM -- For Industry Day A Conformance Checker Tool CSPConCheck -- SmartTestGen+: A Test Suite Booster for Enhanced Structural Coverage -- Model Checking under Fairness in ProB and Its Application to Fair Exchange Protocols -- Model Checking of OSEK/VDX OS Design Model Based on Environment Modeling -- A Cure for Stuttering Parity Games -- Ensuring Reachability by Design -- Approximate Verification and Enumeration Problems -- Undecidability of Quantized State Feedback Control for Discrete Time Linear Hybrid Systems.
Keywords: Computer science; Software engineering; Information theory; Logic design; Computer Science; Logics and Meanings of Programs; Computation by Abstract Devices; Mathematical Logic and Formal Languages; Software Engineering; Programming Languages, Compilers, Interpreters; Theory of Computation